Exploration of cadmium-resistant bacteria in cadmium-contaminated rice fields in Karawang District, Indonesia - NOVRIANTY RIZQI AZIS; YULIA NURAINI; CAHYO PRAYOGO; RIZKY MAULANA ISHAQ (Society for Indonesian Biodiversity, 2024)
Abstract. Azis NR, Nuraini Y, Prayogo C, Ishaq RM. 2024. Exploration of cadmium-resistant bacteria in cadmium-contaminated rice fields in Karawang District, Indonesia. Biodiversitas 25: 3637-3644. Cadmium is a heavy metal naturally present in the soil, but its presence can increase due to human activities (anthropogenic). Increased cadmium content in soil due to human activities can occur due to agricultural activities, such as the continuous use of chemical fertilizers and pesticides. These chemical products contain harmful heavy metals such as cadmium, which results in soil pollution due to the accumulation of these metals in the soil and the entry of these metals into agricultural products, thus affecting health. The problem can be solved by soil bioremediation that utilizes indigenous bacteria. This study aims to explore cadmium-resistant bacteria with high resistance levels that can be used for the bioremediation of cadmium-contaminated soil. Cadmium-resistant bacteria were explored from 4 locations in Karawang District, Indonesia, with soil cadmium content >0.5 ppm, namely 2 locations in Telukjambe Village, 1 in Purwajaya Village, and 1 in Lemahmukti. 14 cadmium-resistant bacterial isolates with different characteristics were obtained from these 4 locations. Microbiological tests conducted include Gram staining test, resistance test, pathogenicity test, and bacterial DNA test. Seven bacterial isolates were found to be non-pathogenic to humans and plants. The best three bacterial isolates from 7 non-pathogenic isolates with resistance ability 50-500 ppm can potentially be used as a bioremediation of cadmium-contaminated soil. The three isolates are isolates B1, B6, and B12. DNA test results stated that isolate B1 is Shewanella decolorationis strain NSSD01, B6 is Chryseobacterium cucumeris strain E1-3, and B12 is Aeromonas hydrophila strain GX5.